COMMUNITY STRUCTURE OF MACROZOOBENTHOS IN SOUTH BIAK WATERS, BIAK, PAPUA - Andriani Widyastuti (Pusbindiklat - LIPI, 2013)
The existence of macrozoobenthos in an coastal waters, can be used as indicators the physical quality of water. The aim of this study is to analyze the diversity and community structure of macrozoobenthos in coastal waters of South Biak waters. Research was conducted in Maret-Nopember 2011, in the coastal waters of South Biak. Sampling using a transect quadrant. Macrozoobenthos samples was preserve in formalin solution 10% and was identified in the laboratory. The value of diversity, similarity and dominance will be calculated from the data, and its relationship with environmental factors. The results was found 101 species by 3572 the number of individuals who are scattered in four stations (Paray, Ambroben, Yenures, and Sorido stations). Makrozoobenthos types were found consisting of four phyla (Annelida, Arthropoda, Echinodermata and Mollusca) derived from 8 classes of Polichaeta, crustaceans, Ophiuroidea, Echinodermata, Holothuroidea, Amphineura, Gastropoda and Bivalves. Value index of diversity (H ‘) ranged between 1, 1354 to 2.8011, Paray and Sorido waters are not polluted waters, and waters Ambroben and Yenures is being polluted waters. Uniformity value (E) ranged from 0.3407 to 0.7666, indicating the existence of species that dominate (approaching 0) and shows the uniformity of all types in the population (approaching 1).